WI-FI-BASED INTERNET OF THINGS (IOT) DATA COMMUNICATION PERFORMANCE IN DENSE WIRELESS NETWORK TRAFFIC CONDITIONS - Michael Ardita; Mira Orisa (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2021)
Currently, there are many Internet of Things (IoT) devices that use Wi-Fi networks to connect to the Internet. As the Wi-Fi network frequency band is used by many parties, the possibility of disconnecting the Internet connection with IoT devices is still high. In this research, we explored the performance of IoT on Wi-Fi networks in high traffic conditions. System testing in this study was carried out using several IoT devices at different distances from the AP. The experimental environmental conditions were also formed so that the Wi-Fi traffic was quite high, generated by software from several laptops. The test results showed that the packet loss in very crowded traffic conditions reached 100%. Round trip time (RTT) data transmission delay of less than 10 ms during normal conditions increased to thousands of milliseconds when the Wi-Fi network conditions were very heavy.